Study on optimization strategy for hybrid underlay/overlay spectrum sharing based on queuing model - Jian-ping LIU; Shun-fu JIN; Bao-shuai WANG (Tongxin xuebao)
In order to improve the licensed spectrum utilization in cognitive radio networks,and provide higher experience quality to system users,the optimizing strategies of the hybrid underlay/overlay spectrum sharing mode was studied.For secondary users,a queuing model with service time following two phase order exponential distribution was constructed,and a method to obtain the steady state distribution was presented for the system model.Based on reward-cost structure,individual optimization strategy with observable case and the Nash equilibrium strategy with unobservable case were discussed.With purpose of optimal social benefit and maximal spectrum incomes,the pricing policies for secondary users to use licensed spectrum were formulated.Using the system experiment,the relations among the different optimal strategies were investigated,and the rationality of the price mechanism was verified.By contrasting the optimal social benefits gained by hybrid underlay/overlay spectrum sharing mode，overlay spectrum sharing mode and underlay spectrum sharing mode,it is further shown that the social optimization strategy of hybrid overlay/underlay sharing mode is more effective and stable to fully use the spectrum resource.